Corrosive characteristics of bioethanol and gasoline blends for metals - Thangavelu, S.K.; Ahmed, A.S.; Ani, F.N. (John Wiley and Sons Ltd, 2016)
Corrosive characteristics of lignocellulosic bioethanol on metals, such as mild steel, copper, and aluminum were studied by static immersion test at room temperature. Effect of metals on degradation of fuel properties, such as pHe, total acid number, acidity, density, viscosity, calorific value, flash point, and color changes were evaluated. Moreover, the transformation of water content and oxidation products in the fuel were investigated. Effect of fuel blends on corrosion rate, chemical structure of metals, and morphology of corrosion product were also examined. Results showed that the corrosion of metals in E50 (50% bioethanol and 50% gasoline) is high compared with E25 and E0. Moreover, degradation of fuel properties and compositional changes in E25 and E50 were high compared with E0. The corrosion rate of aluminum in E50 (0.216mpy) was lower than copper (0.441mpy) and mild steel (0.487mpy). Moreover, the corrosion rate of aluminum in E25 (0.096mpy) was also lower than copper (0.285mpy) and mild steel (0.297mpy). It was discovered that corrosion of materials and degradation of fuel properties were 2.4 times high in higher ethanol blends (above E25) compared with lower ethanol blends (up to E25).